OPTIMIZATION OF BIODIESEL-ETHANOL BLENDS FOR IMPROVED ENGINE PERFORMANCE AND REDUCED EMISSIONS IN COMPRESSION IGNITION ENGINES - Singh, Gajendra; Bentham, John Robins; Kumar, Kapil; Singh, Priyanka; Kumar, Kshitij; Murtaja, Mohd; Kumar, Vijai (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Alternative and sustainable fuel sources must be investigated due to the increasing demand for energy and the depletion of fossil fuel stocks. The utilization of biodiesel-ethanol blends stabilized with ethyl acetate as diesel replacements in compression ignition engines is examined in this study. Stable blends of biodiesel and ethanol (2000 proof) were made and tested, and karanja oil was used as the biodiesel source. A 3.74 kW diesel engine was used to assess many factors, such as fuel characteristics, engine performance, and exhaust pollutants. The created blends performed similarly to diesel, according to the results, with stable combustion and acceptable emissions profiles. Particular results included 3.674–3.684 kW of brake power, 2.003–2.071 l/h of fuel consumption, and lower nitric oxide (NO) emissions when compared to pure diesel. These findings affirm the potential of biodiesel-ethanol blends as viable alternatives to conventional diesel, contributing to energy sustainability and reduced environmental impact.